Middle Years Teachers’ Critical Literacy Practices as Cornerstones of Their Culturally Relevant Pedagogies (LEARNing Landscapes, 2021)
Critical literacy is widely accepted as an important element of culturally relevant pedagogy. In this article, we detail results of a study into how six teachers in rural Eastern Canada purposefully incorporated critical literacy into teaching and learning activities in their classrooms from a culturally relevant pedagogical stance. Findings highlight teachers’ intentional planning that embeds critical literacy, critical literacy in the wider community, and use of multimodal practices in teaching for critical literacy. The critical literacy practices of these teachers reflect their thinking about knowledge and knowledge construction as one key aspect of their culturally relevant pedagogy.
Keywords: critical literacy; culturally relevant pedagogy; middle years classrooms